Measuring Effectiveness of Non-Motorized Vehicles on Spatial Extent for TOD Development: A Case Study for MRT 6 in Dhaka (MIST International Journal of Science and Technology, 2023)
To improve the effectiveness of conventional walking-based Transit-Oriented Development (TOD), introducing Non-Motorized Vehicles (NMV)-based TOD will be a more efficient alternative since it will increase the spatial extent of the TOD node’s buffer area. This paper discusses the available Bicycle-based TOD (BTOD) concept. Based on this concept, the spatial extent of NMV-based TOD (NTOD) has been calculated. A trip-based survey has been conducted on the selected regions of Dhaka along the line of MRT 6 regarding who uses NMV (Rickshaw, Bicycle) and public transport (PT) for his daily commuting. A trip chain analysis was performed first to capture the trip pattern of daily commuters. From the trip chain analysis, it has been found that PT-based trip chains dominated the city’s entire trip chain. Consequently, it has also been found that walking-only and walking-NVM accessible trips dominate 32% and 23% of the entire PT trip chains. However, based on the findings of trip chain analysis to calculate the spatial extent by developing regression models, it has been observed that the access trip length for walking ranges from 1.2-1.4 km, whereas the access trip length for NVM ranges from 4-4.7 km. In Dhaka, the catchment area of NTOD can increase the accessibility potentially by spatial extent expansion of about 70% from the conventional TOD. Therefore, it can be inferred that NVM will give more spatial accessibility than walking. As a result, a new window of planning and design strategies will be opened for the planners and policymakers around TOD station area planning considering NMV. Along with strategic recommendations, limitations, and future research agendas have also been discussed in this paper.MIJST, Vol. 11, June 2023 : 1-10DOI: https://doi.org/10.47981/j.mijst.11(01)2023.368(01-10)